2001
DOI: 10.1038/nn720
|View full text |Cite|
|
Sign up to set email alerts
|

Neurotrophins use the Erk5 pathway to mediate a retrograde survival response

Abstract: Growth factors synthesized and released by target tissues promote survival and differentiation of innervating neurons. This retrograde signal begins when growth factors bind receptors at nerve terminals. Activated receptors are then endocytosed and transported through the axon to the cell body. Here we show that the mitogen-activated protein kinase (MAPK) signaling pathways used by neurotrophins during retrograde signaling differ from those used following direct stimulation of the cell soma. During retrograde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
339
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(356 citation statements)
references
References 36 publications
14
339
0
3
Order By: Relevance
“…It is pertinent to mention that recently we observed that the level of NGF was decreased in the hippocampus of suicide subjects (Dwivedi et al, 2005). Interestingly, it has been reported that internalization and retrogate transport of TrkA, receptors for NGF, activates specifically the ERK5 signaling pathway in neurons (Watson et al, 2001). Also, it has been shown that Epac suppresses muscle-specific A-kinase anchoring protein-associated ERK5 activity in a PKA-independent manner (Dodge-Kafka et al, 2005), and recently, we reported that Epac level is increased in postmortem brain of suicide subjects (Dwivedi et al, 2006).…”
Section: Erk5 Signaling and Suicide Y Dwivedi Et Almentioning
confidence: 72%
See 2 more Smart Citations
“…It is pertinent to mention that recently we observed that the level of NGF was decreased in the hippocampus of suicide subjects (Dwivedi et al, 2005). Interestingly, it has been reported that internalization and retrogate transport of TrkA, receptors for NGF, activates specifically the ERK5 signaling pathway in neurons (Watson et al, 2001). Also, it has been shown that Epac suppresses muscle-specific A-kinase anchoring protein-associated ERK5 activity in a PKA-independent manner (Dodge-Kafka et al, 2005), and recently, we reported that Epac level is increased in postmortem brain of suicide subjects (Dwivedi et al, 2006).…”
Section: Erk5 Signaling and Suicide Y Dwivedi Et Almentioning
confidence: 72%
“…It is widely expressed in many tissues, with the highest levels in the brain Yan et al, 2003). In neurons, ERK5 is activated by neurotrophins, including brain-derived neurotrophic factor (BDNF), neurotrophin (NT)-3, and NT-4 (Cavanaugh et al, 2001;Watson et al, 2001;Liu et al, 2003;Shalizi et al, 2003). A number of other extracellular stimuli, such as epidermal growth factor and G-protein-coupled receptors, also activate ERK5 (Kato et al, 1998;Marinissen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…93 Nevertheless, WNK1 activates Erk5, 94 and Erk5 is a critical mitogen-activated protein kinase required for retrograde NGF/TrkA survival signaling in NGF-dependent neurons. 95 Alterations in WNK1-mediated activation of Erk5 could lead to altered sensory and sympathetic neuron survival in HSAN2 caused by WNK1 mutations. Figure 1 Elp1 is localized in a vesicular pattern in neurites and is mutated in humans with FD and a mouse model that emulates the human mutation.…”
Section: Growth Factor Signalingmentioning
confidence: 99%
“…CREB phosphorylation may also occur downstream from NCAM-dependent autocrine GDNF-mediated signaling in SCs thus contributing to the SC proliferation observed in the compression and epineurotomy models (Iwase, et al 2005). pCREB was not colocalized to axons, but nuclear CREB phosphorylation secondary to long-range signaling through retrograde shuttling of receptor-ligand complexes was not evaluated (Riccio, et al 1997, Watson, et al 2001). …”
Section: Discussionmentioning
confidence: 99%